Turnaround Strategies in Established Small Family Firms - Cater, John; Schwab, Andreas (Family business review, 2008)
This study employs a case-study approach to identify unique characteristics of established small family firms that affect their ability to initiate turnaround strategies when encountering an organizational crisis. In our case studies, we found evidence for family firms employing the standard strategies of top-management changes, infusion of external management expertise, and retrenchment that have been proposed in the general turnaround literature. The implementation of these strategies was, however, moderated by eight characteristics generally associated with family firms, including strong ties to the family firm, internal orientation, altruistic motives, and long-term goal orientation. The introduced framework contributes to a more fine-grained understanding of the turnaround challenges of established family firms and how they can be addressed. This is a topic of substantial practitioner interest considering the high failure rates of family firms.